Young men, masculinities and sex education - Limmer, Mark (Sex Education : Sexuality, Society and Learning, 2010)
This paper draws on focus group and interview data from 45 young men from the north of England to explore the barriers to effective sex and relationships education (SRE). Recent policy debates in relation to establishing statutory SRE in schools provide an opportunity to revisit how it is currently delivered to, and received by, young men. The paper considers the central role played by masculinities and how this role is mediated by social exclusion and poor engagement; it is suggested that addressing masculinities directly should be a priority for future SRE. In conclusion, some tentative approaches to addressing the issues are suggested.
Keywords: 2000 à aujourd'hui; 2000-2009; angleterre; discipline; europe; hommes*; jeunes adultes; masculinité; périodes historiques; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis